Financial Management of Village-owned Enterprises Affected by Employee Competency and Organizational Culture - Abdullah, Faisal; Muhammad, Mediaty; Mas'ud, Anis Anshari (MANDAR: Management Development and Applied Research Journal, 2024)
This study reveals new dynamics in BUMDes financial management by identifying the role of employee competence and organizational culture in managing the financial affairs of Village-owned Enterprises. The objective of this research is to test the hypothesis regarding the influence of employee competence and organizational culture variables on BUMDes financial management. The population in this study consists of 800 BUMDes managers in the city of Parepare. The data collection method employed in this research is a survey method, using structured questionnaires distributed through purposive sampling techniques. Employee competence positively affects BUMDes financial management; higher competence levels are associated with increased financial management accountability in BUMDes. Organizational culture also positively influences BUMDes financial management, as it creates a supportive work environment, clarifies vision and mission, and provides incentives for good performance. These findings offer a new perspective on the importance of organizational culture in managing the contributions of various factors to BUMDes financial management.